THE STRUCTURE OF THE VIRAL TRIGGERS OF FEBRILE SEIZURES IN CHILDREN OF EARLY AGE - M. A. Stroganova; G. P. Martynova; N. A. Shnayder; A. A. Kolodina (LLC "Diagnostics and Vaccines", 2016)
The study presents the results of clinical and laboratory observations 121 children aged 3 to 36 months with the diagnosis «ARVI with convulsive syndrome».  The prevalence of patients with burdened hereditary anamnesis for the development of febrile seizures (FS) (31.4 ± 4.2%). During the laboratory examination along with the respiratory viruses group noted the high herpes virus infection (51.2%), particularly human herpes virus 6 type (of 38.7%). The extension of the spectrum of the diagnostic examination of children  with FS will establish  the role of infectious triggers in the occurrence of FS and thereby define rational tactics and dispensary observation of this group of patients.